A Comparative Taphonomic Analysis of 24 Trophy Skulls from Modern Forensic Cases1, 2. Issue 5 (1st February 2017) - Yucha, Josephine M.; Pokines, James T.; Bartelink, Eric J.
Abstract: Cranial remains retained from fallen enemies are commonly referred to as "trophy skulls, " and many such crania were acquired as souvenirs by U.S. servicemembers during WWII and the Vietnam conflict. These remains increasingly have become the subject of forensic anthropological analysis as their possessors, typically veterans or their relatives, try to discard or repatriate them. The present research uses a qualitative analytical approach to review 24 cases of reported trophy skulls (14 previously unpublished cases and 10 from the literature) to determine which perimortem and postmortem characteristics are most useful for generating a taphonomic profile. Overall, the taphonomic signature of trophy remains includes traits relating to acquisition and preparation, ornamental display, and subsequent curation. Contextual evidence and the biological profile also are considered when determining the possible origin of human cranial remains as a trophy skull. Thorough taphonomic analysis will aid in identifying these types of remains as trophy skulls.